Geographic modeling and simulation systems for geographic research in the new era: Some thoughts on their development and construction - Chen, Min; Lv, Guonian; Zhou, Chenghu; Lin, Hui; Ma, Zaiyang; Yue, Songshan; Wen, Yongning; Zhang, Fengyuan; Wang, Jin; Zhu, Zhiyi; Xu, Kai; He, Yuanqing (Science China. Earth sciences, 2021)
Regionality, comprehensiveness, and complexity are regarded as the basic characteristics of geography. The exploration of their core connotations is an essential way to achieve breakthroughs in geography in the new era. This paper focuses on the important method in geographic research: Geographic modeling and simulation. First, we clarify the research requirements of the said three characteristics of geography and its potential to address geo-problems in the new era. Then, the supporting capabilities of the existing geographic modeling and simulation systems for geographic research are summarized from three perspectives: Model resources, modeling processes, and operational architecture. Finally, we discern avenues for future research of geographic modeling and simulation systems for the study of regional, comprehensive and complex characteristics of geography. Based on these analyses, we propose implementation architecture of geographic modeling and simulation systems and discuss the module composition and functional realization, which could provide theoretical and technical support for geographic modeling and simulation systems to better serve the development of geography in the new era.